Practice of Administrative and Jurisdictional Activity of Community Police Officers – Integral Part of the Principles for the Formation of Local and State Security Policy (Law and Safety, 2021)
The author has accomplished the analysis of the essence of organizational and legal principles of community police officers’ activity (hereinafter – CPO), their interaction with other divisions of the National Police of Ukraine, state authorities, local self-government agencies and communities. The author has analyzed a set of tasks, functions and powers of CPO and the current state of regulatory legal provision of community police officers activity: has outlined the algorithm of actions of community police officers within the combination of functions of district police officers and patrol police officers.The author has outlined the perspectives for more effective involvement of local residents into formation of local and state security policy through new mechanisms of cooperation with local communities and civil society institutions developed by the practice of police officers of territorial communities; the author has provided a number of propositions for the development of regulatory legal documents that would regulate the activities of community police officers. The author has studied the essence of interaction of police officers and members of the community, its legal principles and forms of realization, problems of regulation of the activity of the newly created law enforcement institution.A new format of work of a district police officer, based on the principles of combining the efforts of local self-government agencies and law enforcement agencies, has been characterized. The author has defined a number of gaps in the legislative and regulatory provision of community police officers’ activities, including the establishment of effective coordination between community police officers and local communities and the elimination of existing or possible competitive interest that may arise in the process of their joint activities.The determinant of lag of performing professional activity by community police officers from the standards of similar services of the European Union countries has been defined.
Keywords: a community police officer; National Police of Ukraine; interaction; partnership; community.